PEMBUATAN TABEL MORTALIA MELALUI MODEL LEE CARTER - Taofik Hidayat (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The Lee-Carter model, proposed in 1992, is one of the most well-known methodologies for modeling mortality rates. This model is known for its simplicity and has been used successfully in America, Japan, and Australia. Basically, the Lee-Carter model is a regression model. However, the independent variables are not given explicitly so an approximation is made. They proposed a singular value decomposition. As a case study, secondary data was taken from the final project in the Department of Mathematics ITB